2013
DOI: 10.4236/fns.2013.410131
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid (5-ALA): Analysis of Preclinical and Safety Literature

Abstract: Problem: 5-ALA has been used for many years at relatively high dose amounts in single doses for photodynamic therapy and immunofluorescence of tumors. An analysis of compiled data relating to safety and any side-effects about the use of 5-ALA at low doses has not yet been published. Purpose: This report analyzes data about the safety of the use of 5-Aminolevulinic Acid (5-ALA) in low doses as a supplement over an extended period of time. Methods: This investigation is a systematic analysis of the current liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Although an extremely large iron dosage can cause hepatotoxicity as well as gastrointestinal disturbances, a maximum safety level for a repeated dose is indicated as 1,000 mg/kg/day SFC in rats in the generally recognized as safe (GRAS) notice of FDA in the United States, which was then approved as a food ingredient ( 45 ). In addition, the safety of ALA/SFC as a dietary supplement has been reviewed ( 46 ); the safety features of ALA/SFC have also been shown in a study with type II diabetes patients under the therapy with antidiabetes drugs ( 47 ). From the viewpoint of these high levels of safety of ALA/SFC, it is expected that ALA/SFC-based combination therapies with conventional drugs (e.g., ALA/SFC with artemisinin) can be available to reduce the dosage of conventional ones.…”
Section: Discussionmentioning
confidence: 99%
“…Although an extremely large iron dosage can cause hepatotoxicity as well as gastrointestinal disturbances, a maximum safety level for a repeated dose is indicated as 1,000 mg/kg/day SFC in rats in the generally recognized as safe (GRAS) notice of FDA in the United States, which was then approved as a food ingredient ( 45 ). In addition, the safety of ALA/SFC as a dietary supplement has been reviewed ( 46 ); the safety features of ALA/SFC have also been shown in a study with type II diabetes patients under the therapy with antidiabetes drugs ( 47 ). From the viewpoint of these high levels of safety of ALA/SFC, it is expected that ALA/SFC-based combination therapies with conventional drugs (e.g., ALA/SFC with artemisinin) can be available to reduce the dosage of conventional ones.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it was also reported that ALA significantly increased fruit interior quality (Gao et al, 2013; Zhang L. Y. et al, 2015). Furthermore, ALA is readily biodegradable and has no adverse effects on animals and humans (Perez et al, 2013). Therefore, ALA can simultaneously improve fruit coloration and fruit interior quality without any detrimental effects, suggesting great application prospect in fruit production.…”
Section: Introductionmentioning
confidence: 99%
“…The oral doses of 5‐ALA chosen in our mouse studies were based on allometric scaling (i.e. by surface area) of the doses typically used (10–60 mg·kg −1 ) for photodynamic therapy and immunofluorescence of tumours in patients (Regula et al ., ; Webber et al ., ; Ackroyd et al ., ; Hinnen et al ., ; Perez et al ., ). As a result, similar concentrations of 5‐ALA would be expected initially in the gastrointestinal tract for both species, being on the order of 10–100 mM.…”
Section: Discussionmentioning
confidence: 97%